2020
DOI: 10.1002/pc.25877
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling and experimentally optimizing synergistic effect on thermal conductivity enhancement of polyurethane nanocomposites with hybrid carbon nanofillers

Abstract: Combining various carbon nanofillers with different dimensions can lead to a synergistic effect through the formation of an efficient conductive network. Hybrid polyurethane (PU) nanocomposites containing multi-walled carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs) were fabricated to study experimental and theoretical aspects of thermal conductivity (TC) enhancement. The optimization of hybrid nanofillers combinations was done to synergically enhance the TC using various types of graphene, nanofill… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…[ 29 ] The tensile strength of SBR/4phr BNNS‐CNT is increased to 3.37 ± 0.29 MPa, corresponding to an elongation at break of 776.8% ± 21%, which is due to the synergistic effect generated between the two nanofillers with different geometries, enhancing the stress transfer between the polymer and the nanofillers. [ 30 ] However, as shown in Figure 7A and Table 3, the tensile strength of SBR/4phr BNNS is 1.72 ± 0.24 MPa, which is lower than the tensile strength of the nanocomposites with 2 and 3 phr BNNS. It is shown in Figure 5A that BNNS, as a small‐sized nanofiller, tends to aggregate as its content in the matrix increases, which will lead to weak interfacial bonding and insignificant enhancement on the nanocomposites.…”
Section: Resultsmentioning
confidence: 88%
“…[ 29 ] The tensile strength of SBR/4phr BNNS‐CNT is increased to 3.37 ± 0.29 MPa, corresponding to an elongation at break of 776.8% ± 21%, which is due to the synergistic effect generated between the two nanofillers with different geometries, enhancing the stress transfer between the polymer and the nanofillers. [ 30 ] However, as shown in Figure 7A and Table 3, the tensile strength of SBR/4phr BNNS is 1.72 ± 0.24 MPa, which is lower than the tensile strength of the nanocomposites with 2 and 3 phr BNNS. It is shown in Figure 5A that BNNS, as a small‐sized nanofiller, tends to aggregate as its content in the matrix increases, which will lead to weak interfacial bonding and insignificant enhancement on the nanocomposites.…”
Section: Resultsmentioning
confidence: 88%
“…However, the enhancement in decomposition temperature was higher for the nanocomposite with solely GNP-S750, compared to hybrid MWCNT/GNP-S750 (Figure 1(a) inset), which is attributed to the higher thermal conductivity of hybrid MWCNT/GNP-S750 in the PU matrix, in comparison with PU/GNP-S750. 11 Hybrid MWCNT/GNP-S750 nanocomposite lost weight at lower temperatures compared to PU/GNP-S750, owing to higher heat flow throughout the specimen. This means that thermal conductivity enhancement dominated improved nanofillers dispersion in hybrid nanocomposites.…”
Section: Resultsmentioning
confidence: 98%
“…35 This 3D hybrid architecture promoted the interaction of nanofillers with PU matrix, in which the enhanced contact area facilitated the load transferring through the nanofillers. 10,11,26 In addition, the elastic modulus of PU (∼72 MPa) is increased up to about 39%, 42% and 52% for nanocomposites with MWCNTs, GNPs and MWCNTs/GNP-S750s, respectively.
Figure 5.Dynamic mechanical analysis storage modulus of (a–d) hybrid MWCNTs/GNPs nanocomposites versus temperature and (e–f) storage modulus in the glassy region (25°C).
…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…11 Different studies have suggested that the k of graphene and carbon nanotubes are in the range of 1950-6500 W m À1 K À1 at room temperature, which are values among the highest known. 36 As NFs, they present a k even greater than those predicted by theories and models. In 2001, Choi et al reported that for a nanotube loading of and below 0.3 volume fraction in oil, the k ratio is similar to Cu NPs in the same fluid.…”
Section: Introductionmentioning
confidence: 82%